OBSERVATIONS ON THE EFFECT OF PENICILLIN ON THE REACTION BETWEEN PHAGE AND STAPHYLOCOCCI - Krueger, A. P. (The Rockefeller University Press, 1948)
The essential facts relating to the reaction between phage, sodium penicillin G, and the K race of Staphylococcus aureus are: 1. Except when [P] is very high, massive lysis of the cellular substrate occurs considerably sooner in the P-PN-B mixture than in preparations containing P alone or PN alone. 2. The accelerative effect is present in concentrations of PN varying from 0.1 to 1 x 10(4) units/ml. 3. Acceleration of lysis can be secured by exposing staphylococci to PN prior to treatment with P. 4. In certain concentrations of P and B in tryptose-phosphate broth, P formation apparently takes place without bacterial reproduction. The extent to which P is produced is influenced very little by [PN](0) but is markedly dependent upon [P](0). With low P/B ratios the [P] curve shows a lag followed by a rapid rise to a peak of 25 to 30 times [P](0). When the P/B ratio approaches unity there is a considerable primary drop in [P] and later an increase which, however, fails to bring the total P produced above [P](0). When P/B is still higher, the [P] curve drops profoundly as the bacteria lyse and never enters into a productive phase. 5. In Locke's solution mixtures of P-PN-B, containing 5 to 10 per cent broth, P formation occurs in the absence of detectable cellular reproduction to the extent of a four- to sixfold increase over [P](0). 6. Direct microscopic examination of wet preparations removed during the P-PN-B reaction has disclosed swelling of the staphylococci. The swollen cells are three times the diameter of normal S. aureus secured from an 18 hour culture. Cellular swelling apparently accounts for the experimental observation that the curve for lysis plotted from [B](K) lags considerably behind the [B](D) curve. Increase in the size of individual cells would tend to keep the photoelectric colorimeter measurements high even while the direct count was diminishing. 7. When the P-PN-B reaction is carried out in broth, attainment of the peak in P production is followed by a moderate loss of P. This does not occur when P, PN, and B react in Locke's solution. The reaction dealt with here between P, PN, and S. aureus is similar in a good many respects to that investigated by Price for P, PN, and S. muscae. For example, in both cases P is produced without bacterial reproduction. There are, however, certain noteworthy differences: (a) PN increases the time of half-lysis for S. muscae and lessens it for S. aureus. (b) The yields of P in ranges of [P] and [PN] permitting P formation without bacterial reproduction are higher for S. muscae than for S. aureus. (c) An increase in [PN] from 33 units/ml, to 833 units/ml, greatly reduces the final plaque count secured with S. muscae as a substrate but has no discernible influence on the reaction when S. aureus is used. Currently studies are in progress on the P-PN-B reaction in a synthetic medium in order to obtain information on the mechanism involved.